Reimagining Islamic education: Critical perspectives inspired by Nurcholish Madjid - Siroj, Mohamad; Ulfah, Ni’matul (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
Islamic education in Indonesia has experienced significant transformations in response to evolving social, political, and cultural dynamics. Nurcholish Madjid's progressive and inclusive ideas offer a critical framework for rethinking Islamic education in the context of modern challenges. This study aims to analyze Madjid's concept of critical Islamic education, assess its relevance to Indonesia's contemporary Islamic education system, and explore its potential application in modern educational settings. Employing a qualitative methodology with a literature review approach, the research focuses on Madjid’s writings and intellectual contributions. The findings reveal that Madjid envisions Islamic education as a means to cultivate not only religious devotion but also critical thinking and active participation in democratic society. He emphasizes pluralism and the integration of religious sciences with social sciences and humanities to foster comprehensive understanding, creativity, and innovation. Additionally, his approach highlights the importance of developing critical awareness to navigate social and political complexities. In conclusion, Madjid’s concept of critical Islamic education provides a transformative paradigm that shifts the focus from quantity to quality. By embracing principles of democracy, pluralism, and humanistic values, Islamic education can nurture faithful, knowledgeable, and socially responsible individuals capable of contributing to a just and inclusive society.